O mundo do trabalho nas perspectiva dos sujeitos da educação de jovens e adultos: um estudo sobre os cadernos pedagógicos de Belo Horizonte e Betim - Eloiza Lagaris de Paula Ribeiro (2024)
The present study aims to analyze the problem situations described in the Pedagogical Notebooks of Belo Horizonte and Betim produced by teaching professionals who work in Youth and Adult Education (EJA) in the respective cities. Based on narrative research, we sought to highlight the perspectives of the subjects who work in this educational modality. To characterize the field of study, it was also highlighted who the EJA subjects presented by Cadernos are and what types of work are available to them in a scenario marked by profound changes. To analyze the empirical material, the work was based on authors with research concerning the world of work, production of teaching materials for Youth and Adult Education and education from the perspective of human rights, highlighting Miguel Arroyo, Leôncio Soares, Ricardo Antunes and bell hooks. The work verified the strength of the discourse of entrepreneurship in the school environment, shaping ways of thinking, feeling and acting on the part of the subjects of Youth and Adult Education.